2012
DOI: 10.1007/s13197-012-0672-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of thuja (Thuja occidentalis) cones and peach (Prunus persia) seeds in raw chicken ground meat during refrigerated (4 ± 1 °C) storage

Abstract: The antioxidant activity of thuja (Thuja occidentalis) cones extract (TCE) and peach (Prunus armeniaca) seeds extract (PSE) were estimated by DPPH free radical scavenging activity method. Total phenolics, total flavonoids and reducing power were also estimated in these extracts. Antioxidant potential of these by products was also evaluated in raw chicken ground meat (GM) during refrigerated (4±1°C) storage. Total phenolics in TCE and PSE were 7.80±0.04 and 1.92± 0.04 mg TAE/gdw respectively. Both extract also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
7
23
0
Order By: Relevance
“…Plant-based food items contain a wealth of phytochemicals, and many have antioxidant properties (Halliwell et al 1995;Hollman and Katan 1997;Yogesh and Ali 2012). Grains, fruits and vegetables have been considered as excellent sources of antioxidants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant-based food items contain a wealth of phytochemicals, and many have antioxidant properties (Halliwell et al 1995;Hollman and Katan 1997;Yogesh and Ali 2012). Grains, fruits and vegetables have been considered as excellent sources of antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamins C and E, Phenolic compounds and carotenoids have been thought to be responsible for most of the antioxidant activity in foods (Esterbauer et al 1991;Jialal et al 1990;Duthie and Crozier 2000). Many workers recently reported antioxidative effect of aqueous extract of some plant and fruit byproducts in meat and meat products (Yogesh and Ali 2012;Naveena et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies confirmed the presence of monoterpenes and diterpenes in cell culture of Thuja showing thujone-rich fraction possessing anticancer activity against A375 cells [9]. It is also found to possess the hepatoprotective [10], antibacterial [11], and antifungal activities [12]. Thuja has also been reported to possess potential to inhibit the activity of HIV-1 virus and common cold virus [6] and its protective effect against toxicity induced by radiation is also reported [13].…”
Section: Introductionmentioning
confidence: 79%
“…Antioxidants vary widely in chemical structure and have varied mechanisms of action. The key mechanism is their reaction with free radicals to form relatively stable inactive products 21 . Thus, antioxidants delay lipid oxidation by scavenging free radicals which are generated in the initiation phase, propagation phase, or during the breakdown of the hydroperoxides.…”
Section: Introductionmentioning
confidence: 99%